2021
DOI: 10.1103/physrevd.104.043519
|View full text |Cite
|
Sign up to set email alerts
|

Loop decay in Abelian-Higgs string networks

Abstract: We study the decay of cosmic string loops in the Abelian-Higgs model. We confirm earlier results that loops formed by intersections of infinite strings formed from random-field initial conditions disappear quickly, with lifetimes proportional to their initial rest-frame length, l init . We study a population with l init up to 6000 inverse mass units and measure the proportionality constant to be 0.14 AE 0.04, independently of the initial lengths. We propose a new method to construct oscillating nonself interse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 43 publications
3
44
2
Order By: Relevance
“…The main differences concern the number density of small loops and the treatment of gravitational backreaction, which can smooth out string singularities. Moreover, the entire picture of NG string loops decaying by gravitational radiation has been challenged by fieldtheoretic simulations suggesting a much faster decay of the network whose origin, however, remains mysterious [4,14]. In this paper, we follow the approach in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The main differences concern the number density of small loops and the treatment of gravitational backreaction, which can smooth out string singularities. Moreover, the entire picture of NG string loops decaying by gravitational radiation has been challenged by fieldtheoretic simulations suggesting a much faster decay of the network whose origin, however, remains mysterious [4,14]. In this paper, we follow the approach in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Hence if the SGWB reported by NANOGrav is due to Abelian-Higgs cosmic strings, a fraction of those loops are Nambu-Goto-like and survive to radiate gravitationally. Hindmarsh et al (2021) find that this fraction needs to be between 10 −3 and 0.1.…”
Section: A Review Of Current Limits On the Cosmic String Tensionmentioning
confidence: 92%
“…However, the results obtained from simulations of string networks seem to describe a different behaviour [32]. It has also been suggested that internal degrees of freedom found in these models [33] can play a significant role in that case [32,34] 1 . Note, however, that this effect was not observed in [39] where these internal modes do not seem to be clearly excited.…”
Section: Introductionmentioning
confidence: 92%

Internal Excitations of Global Vortices

Blanco-Pillado,
Jiménez-Aguilar,
Queiruga
et al. 2021
Preprint
Self Cite